ThermoSwitch / Puteri Ailhanna Najeehah Zaidi ... [et al.]. - Zaidi, Puteri Ailhanna Najeehah; Azizan, Muhammad Firdaus; Abdullah, Nur Salsabila Mardhiyah; Badrulhisam, Adeeb Bukhori; Nor Hasmawi, Nor Aida Natasha (2025)
The reason we chose the name ThermoSwitch Enterprise is that the word "ThermoSwitch" strongly implies that it focuses on temperature control or sensing technology. Because the prefix "Thermo" is derived from the Greek word "thermos," meaning "heat" or "hot," it instantly links the company to temperature-related problems. Since the word "switch" describes a device that may change states, the company may manufacture or employ temperature sensors or switches to control a variety of systems. This might encompass anything from industrial equipment and thermostats to medical devices and smart home solutions. ThermoSwitch Enterprise is a vibrant business committed to creating cutting-edge, environmentally friendly solutions for contemporary hydration requirements. Understanding the increasing need for adaptability and ease in daily life, we work to develop goods that fit easily into hectic schedules while having as little of an impact as possible on the environment. Providing superior, easy-to-use products that improve the customer experience is at the heart of our guiding principles. Our cutting-edge technologies are made to realise our belief that staying hydrated should be simple and pleasurable. ThermoSwitch Enterprise is dedicated to ongoing research and development in order to maintain its leadership position in the hydration sector. In order to reduce our environmental impact and promote a better future, we give sustainability top priority in the design and production of our products.